Characterization of the thermotolerant cell. II. Effects on the intracellular distribution of heat-shock protein 70, intermediate filaments, and small nuclear ribonucleoprotein complexes (The Rockefeller University Press, 1988)
Here we further characterize a number of properties inherent to the thermotolerant cell. In the preceding paper, we showed that the acquisition of the thermotolerant state (by a prior induction of the heat-shock proteins) renders cells translationally tolerant to a subsequent severe heat-shock treatment and thereby results in faster kinetics of both the synthesis and subsequent repression of the stress proteins. Because of the apparent integral role of the 70-kD stress proteins in the acquisition of tolerance, we compared the intracellular distribution of these proteins in both tolerant and nontolerant cells before and after a severe 45 degrees C/30-min shock. In both HeLa and rat embryo fibroblasts, the synthesis and migration of the major stress- induced 72-kD protein into the nucleolus and its subsequent exit was markedly faster in the tolerant cells as compared with the nontolerant cells. Migration of preexisting 72-kD into the nucleolus was shown to be dependent upon heat-shock treatment and independent of active heat- shock protein synthesis. Using both microinjection and immunological techniques, we observed that the constitutive and abundant 73-kD stress protein similarly showed a redistribution from the cytoplasm and nucleus into the nucleolus as a function of heat-shock treatment. We show also that other lesions that occur in cells after heat shock can be prevented or at least minimized if the cells are first made tolerant. Specifically, the heat-induced collapse of the intermediate filament cytoskeleton did not occur in cells rendered thermotolerant. Similarly, the disruption of intranuclear staining patterns of the small nuclear ribonucleoprotein complexes after heat-shock treatment was less apparent in tolerant cells exposed to a subsequent heat-shock treatment.